Perlindungan Hukum Bagi Investor Terkait Pembubaran Badan Hukum Reksa Dana - I Gede Satyawan Pradnya Wiguna; I Nyoman Budiartha; Desak Gde Dwi Arini (Jurnal Konstruksi Hukum, 2022)
Mutual funds are investment instruments regulated in regulation number 23/POJK/04/2016 concerning mutual funds, as a guide for investment managers in protecting the rights of investors. Lack of carefulness of investors in choosing mutual fund products and determining the right and safe investment manager, so that legal protection is needed for mutual fund investors. The purpose of this study is to reveal the legal protection for mutual fund investors related to the dissolution of the mutual fund management legal entity where investors invest their capital. The method used in this study is a normative legal method with a statutory approach. The technique of collecting legal materials is done by classifying legal materials. Sources of legal materials used are primary and secondary law. After the data was collected, the data were analyzed by descriptive analysis. The results of the study reveal that the legal consequences for investors related to the dissolution of the mutual fund managing legal entity are regulated in Article 50 of the OJK regulation if the mutual fund product is dissolved the investor cannot resell after the dissolution of the mutual fund product. If there is a loss to the mutual fund product caused by the investment manager, the investment manager must be responsible for the loss due to his actions.